Deformation diagrams of amorphous polyimide (kapton H) in the state of moderate and deep cooling: Experiment and theory - Natsik, V.D.; Rusakova, H.V.; Lubenets, S.V.; Lototskaya, V.A.; Yakovenko, L.F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2023)
A comprehensive experimental and theoretical study of the regularities of active deformation at a constant rate of an amorphous polymer at room temperature and the influence of moderate and deep cooling on them was performed. The samples of amorphous aromatic polyimide (an analogue of kapton H) that are randomly cut fragments of the industrially produced thermoplastic film with a thickness of 25 μm were the object of the experimental study. The σ–ε diagrams of the tensile test, where σ and ε= `ε t are the tensile stress and the relative strain, respectively, were recorded for 32 samples at three rates `ε = 7∙10–5 , 7∙10–4 , 6∙10–3 s –1 under three temperatures T = 293, 77, and 4.2 K. In the state of deep cooling at T = 4.2 K, several samples were deformed as brittle glassy bodies – rupture after short elastic deformation. But the majority of the samples at all values of the experimental parameters ( T, `ε) had the rheological properties of rubber-like highly elastic materials (elastomers) with traditional tensile test diagrams: initial stage I of linear elastic deformation σI = Meε with Young’s modulus Me = Me (T) ; stage III of linear highly elastic deformation σIII = σfe + Mhe ε with modulus Mhe = Mhe (T) and conditional limit of elasticity σfe = σfe (T, `ε) ; intermediate stage II of the relaxation type σII (ε; T, `ε) with a nonlinear stress-strain dependence. The σ–ε diagrams of the individual samples with sufficiently high accuracy coincide with the graph of the function σ (ε; T, `ε) which is the solution of the previously derived nonlinear rheological equation (V. D. Natsik and H. V. Rusakova, Fiz. Nizk. Temp. 48, 281 (2022) [Low Temp. Phys. 48, 253 (2022)]; Fiz. Nyzk. Temp. 49, 246 (2023) [Low Temp. Phys. 49, 228 (2023)]). In its derivation, a molecular-kinetic model was used: an amorphous polymer is considered as a set of statistically independent kinetic units, namely, molecular segments, and the elementary act of deformation is caused by thermomechanical activation of nonlinear excitations of these segments called elastons. The elaston mechanism of transformation of the deformation diagrams of amorphous polyimide samples under their moderate and deep cooling is discussed in detail: the transition between deformation states of warm and frozen elastomer, low-temperature effects of structural deformation glass transition and deformation melting. Comparing the results of experiments and theory made it possible to obtain the empirical estimates for the macromechanical characteristics of the studied samples and the microparameters of elaston excitations. A significant and unsystematic (random) scatter of the macro- and micromechanical characteristics of the samples was revealed, which indicates a significant and random heterogeneity of the macro- and microstructure of the polyimide film from which they were made.